Cognitive style and consumer innovativeness - Foxall, Gordon R.; Haskins, Christopher (Cranfield School of Management, 1986)
The identification of consumer innovators offers marketing managers the opportunity to tailor new products to the buyers who initiate the diffusion of innovations. Progress has been made in identifying such consumers in economic and social terms, but there are advantages of cost and convenience in isolating the personality profiles of innovators, especially during prelaunch product testing. But innovative consumers' distinctive personality traits have proved elusive. This paper reports an investigation of innovative brand choice in the context of new food product purchasing which employed the Adaption-Innovation Inventory (KAI). This highly reliable test of cognitive style correlates with several personality traits known to be associated with innovativeness; it also has high validity in the prediction of behaviour over a wide range of contexts. The research reported went beyond the common expectation of a simple, direct relationship between personality and brand choice to investigate the predictive validity of the KAI over a range of product continuity/discontinuity. The results are considerably more encouraging than those of earlier research for the identification of personality/consumer choice links. They suggest an operational measure of product continuity/discontinuity and support the use of the KAI as a viable marketing tool.